Governance Mechanisms and Financial Reporting Quality: The Moderating Role of Leadership Commitment - Tenripada; Andi Mattulada; Abdul Kahar; Andi Chairil Furqan; Muhammad Ikbal Abdullah (Academic Bright Collaboration, 2026)
Purpose – This study examines how internal governance mechanisms and leadership commitment influence the quality of financial reporting in Indonesian local governments. While prior studies emphasize the role of internal control systems and internal audit functions in strengthening public sector accountability, empirical evidence on how leadership commitment interacts with these mechanisms remains limited. This study therefore investigates whether leadership commitment strengthens or alters the relationship between audit findings, internal control maturity, internal audit capability, and financial reporting quality. Methods – This research employs a quantitative approach using panel data from Indonesian local governments. The dataset consists of 2,580 observations derived from audit reports, SPIP maturity assessments, APIP capability evaluations, and local government financial statements. To examine the moderating role of leadership commitment, this study employs Moderated Regression Analysis (MRA) using an interaction approach. Findings – The results show that audit findings are negatively associated with financial reporting quality, whereas SPIP maturity and APIP capability exhibit positive and statistically significant effects. Leadership commitment, proxied by the rate of follow-up on audit recommendations, functions as a conditional moderator. It significantly mitigates the adverse impact of audit findings but simultaneously weakens the positive influence of institutional oversight mechanisms on financial reporting quality.Research implications – The findings highlight that improving financial reporting quality in local governments requires strengthening internal control maturity and internal audit capability while ensuring that leadership commitment reinforces, rather than substitutes, institutional governance mechanisms to sustain effective and credible public financial accountability.Originality – This study contributes to public sector accounting literature by demonstrating that leadership commitment does not always reinforce governance mechanisms and may instead create a decoupling effect between formal institutional controls and financial reporting outcomes.